PENGARUH LATIHAN SHOULDER INTERNAL ROTATION TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA EKSTRAKULIKULER BULUTANGKIS PUTRA SMAN 12 PEKANBARU - Rendy Syafutra; Saripin '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : this research aimed ti find out the effect of shoulder internal rotation to the sterngth of shoulder and arm muscles in badminton extracurricular of male student of SMAN 12 Pekanbaru, so that the student be able to make an smash so the ball could reach the opponent area. The population of this experimental research was the male players of badminton extracurricular of SMAN 12 Pekanbaru. The total number of the active players that joined the training was 10 players. The writer used Total Sampling technique to take the sample where this sampling takes all of the population as the sample (Sugiono, 2008 : 124). The instrument of this research was Expanding Dynamometer, it was aimed to measure the strength of shoulder and arm muscles. Next, the data was processed using statistic and the writer also used the level of significance 0.05α to test the normality by using lilifurs-test. Therefore, the alternative hypothesis was an effect of shoulder internal rotation training to the strength of shoulder and arm muscle in badminton extracurricular of male student of SMAN 12 Pekanbaru. After being analyzed usingt-test formula, the value of tobserve was 11.47 and the value of ttabel was 1.812, so tobserve>ttabel. Based on the data analysis, the averageof pre-test was 19.1 and the average of pos-test was 23.0, so the data was normal. In conclusion, the shoulder intenal rotation training effect the strength of shoulder and arms muscle in badminton extracurricular of male studentof SMAN 12 Pekanbaru.Keyword: Shoulder Internal Rotation, the strength of shoulder and arm muscles.